"Maybe he's on the toy train": empathising and systemising in an encounter with David Macaulay's Black and White. (28th March 2014) - Hardstaff, Sarah
Abstract This study explores the responses of Abby, a young person with autism, to David Macaulay's 1990 picturebook Black and White. Although both picturebook researchers and autism practitioners focus on the importance of encouraging empathetic responses to fictional characters, I build on Louise Collins' argument that Macaulay's work offers an opportunity to develop a different kind of " moral literacy" (2002, p.31). Different ways of practising and understanding perspective‐taking in relation to fiction are considered in light of Abby's responses to Black and White and to fiction more generally. This study, in considering its own weaknesses, also offers a critique of the typical approaches to picturebook research whereby taking the perspective of fictional characters is sometimes seen as indicative of reading competence.